Mollusks, Echnioderms, Coelenterates, etc. Part E [electronic resource] : Rotatoria - Harring, H. K.; Canadian Arctic Expedition (1913-1918) (Ottawa : F.A. Acland, 1921)
Original issued in series: Report of the Canadian Arctic Expedition, 1913-1918 v. 8, pt. E. Includes list of titles in the series. "Southern Party, 1913-1916." Bibliography: p. 15E-16E. Electronic reproduction. Mode of access: Internet. 44